Expression of NOD2 in Paneth cells: a possible link to Crohn's ileitis. Issue 11 (21st October 2003) - Ogura, Y; Lala, S; Xin, W; Smith, E; Dowds, T A; Chen, F F; Zimmermann, E; Tretiakova, M; Cho, J H; Hart, J; Greenson, J K; Keshav, S; et al.
Abstract : Background and aims: Genetic variation in NOD2 has been associated with susceptibility to Crohn's disease (CD) and specifically with ileal involvement. The reason for the unique association of NOD2 mutations with ileal disease is unclear. To identify a possible link, we tested expression of NOD2 in intestinal tissue of CD patients and controls. Patients and methods: Fifty five specimens of ileum or colon from 21 CD patients, seven ulcerative colitis (UC) patients, and five controls with pathology other than CD or UC were stained for NOD2 using an immunoperoxidase method. Results: Using a monoclonal antibody against NOD2 developed in our laboratory, we detected uniform expression of NOD2 in terminal ileum Paneth cells from controls and patients as well as in metaplastic Paneth cells in the colon. Mechanical purification showed enriched expression of NOD2 mRNA in ileal crypts. In Paneth cells, NOD2 was located in the cytosol in close proximity to the granules that contain antimicrobial peptides. We detected minimal NOD2 in the villous epithelium of the ileum or in the colonic epithelium from both CD patients and controls. Conclusions: These results suggest a role for NOD2 in the regulation of Paneth cell mediated responses against intestinal bacteria and a plausible mechanism to explain the selective association of NOD2 mutations with ileal disease. The impaired capacity of CD associated mutations to sense luminal bacteria may result in increased susceptibility to certain gut microbes.